2014
DOI: 10.1371/journal.pone.0103059
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Phenotype Is Associated with Disease Severity in Preterm Infants with Chronic Lung Disease

Abstract: BackgroundThe etiology of persistent lung inflammation in preterm infants with chronic lung disease of prematurity (CLD) is poorly characterized, hampering efforts to stratify prognosis and treatment. Airway macrophages are important innate immune cells with roles in both the induction and resolution of tissue inflammation.ObjectivesTo investigate airway innate immune cellular phenotypes in preterm infants with respiratory distress syndrome (RDS) or CLD.MethodsBronchoalveolar lavage (BAL) fluid was obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 54 publications
5
20
0
1
Order By: Relevance
“…It is therefore proposed here that after hyperoxia exposure, rAMs transdifferentiate into the cells of Pop3, and these activated ‘rAMs’ may causally contribute to arrested alveolarization. This idea is supported by the observations that macrophages from lavage fluids from neonates with BPD exhibit phenotypic plasticity , and that increased expression of MHCII on pulmonary macrophages was noted in lungs from preterm infants who died with BPD . In sum, this is the first report that macrophages are causal contributors to pathological lung development.…”
Section: Resultssupporting
confidence: 53%
“…It is therefore proposed here that after hyperoxia exposure, rAMs transdifferentiate into the cells of Pop3, and these activated ‘rAMs’ may causally contribute to arrested alveolarization. This idea is supported by the observations that macrophages from lavage fluids from neonates with BPD exhibit phenotypic plasticity , and that increased expression of MHCII on pulmonary macrophages was noted in lungs from preterm infants who died with BPD . In sum, this is the first report that macrophages are causal contributors to pathological lung development.…”
Section: Resultssupporting
confidence: 53%
“…AMφs are known to express a unique combination of phenotypic markers due to the influence of the airway microenvironment (2), but few reports have described the immunophenotype of human infant AMφs (23). We measured surface marker expression of AMφs from seven infants and seven adults (Figure 1).…”
Section: Infant and Adult Amφs Express Similar Levels Of M1/m2 Activamentioning
confidence: 99%
“…Preterm infants had increased proportions of non-classical CD14 + CD16 + monocytes at birth, and immature macrophage phenotypes were associated with progression from respiratory distress syndrome to chronic lung disease of prematurity. 75 Preterm infants with resolving lung injury had greater proportions of mature macrophages, than those with progressive lung disease. Since these types of studies rely on lavage of ventilated, intubated babies, there is no information regarding the phenotype of macrophages during normal human perinatal development or on the impact of phenotype on development of asthma in subsequent childhood.…”
Section: Pulmonary Macrophages In Early Lifementioning
confidence: 94%
“…Some studies have used bronchial lavage samples from babies requiring mechanical ventilation during chronic infections, and suggested that phenotypic maturation of monocyte populations was associated with gestational age. Preterm infants had increased proportions of non‐classical CD14 + CD16 + monocytes at birth, and immature macrophage phenotypes were associated with progression from respiratory distress syndrome to chronic lung disease of prematurity . Preterm infants with resolving lung injury had greater proportions of mature macrophages, than those with progressive lung disease.…”
Section: Development Of Immunity In Early Lifementioning
confidence: 99%